"Hey First Nations people! Got a hankerin' for a chunk of B.C.? Well c'mon down to Crazy Glens!.We got deals for you! We're blowing the entire province out the door! No money down and no [.] - Raeside, Adrian (Victoria Times Colonist, 1998)
"Hey First Nations people! Got a hankerin' for a chunk of B.C.? Well c'mon down to Crazy Glens!.We got deals for you! We're blowing the entire province out the door! No money down and no payments,.Ever! You want the Cariboo? Peace River? Vancouver? We got all the big names here at Crazy Glens! No credit? No problem! No legitimate claims? Here at Crazy Glens.We don't care!.And as our doorcrasher special, were throwing in Vancouver Island."